Combination of Transcutaneous Electrical Nerve Stimulation (TENS) at acupuncture points in controlling blood pressure at the Public Health Center in Patrang, Jember - Anita Fatarona; Hella Meldy Tursina; Hendra Dwi Cahyono (Jurnal Kesehatan dr. Soebandi, 2023)
Hypertension or high blood pressure is a major risk factor for stroke, heart failure, and other vascular diseases. Transcutaneous Electrical Nerve Stimulation (TENS) is a non-pharmacological modality therapy that has very minimal side effects. The research design used was a quasy experiment with a pre-test and post-test approach with control group design. This study divided the respondents into 2 groups, namely the intervention group and the control group. Based on the results of the Friedman test, it showed a significant decrease in systolic blood pressure with a p value of 0.000 in the intervention and control groups. As for the diastolic pressure in the intervention group, a significant decrease in blood pressure was found with a p value of 0.033. In the diastolic control group, there was no significant decrease in diastolic blood pressure. The use of TENS at point PC5 PC6 LI4 LI10 showed that it could significantly reduce systolic and diastolic blood pressure in hypertensive patients, while deep breathing therapy showed that only systolic blood pressure decreased significantly. TENS is an alternative intervention that patients can use safely, comfortably, peacefully and can be done independently